Translational Modulation of Proteins Expressed from Bicistronic Vectors - Prasun J. Mishra; Lata G. Menon; Pravin J. Mishra; Philipp Mayer-Kuckuk; Joseph R. Bertino; Debabrata Banerjee (Molecular Imaging)
Bicistronic vectors are useful tools for exogenous expression of two gene products from a single promoter element; however, reduced expression of protein from the second cistron compared with the first cistron is a common limitation to this approach. To overcome this limitation, we explored use of dihydrofolate reductase (DHFR) complementary DNA encoded in bicistronic vectors to induce a second protein of interest by methotrexate (MTX) treatment. Previous studies have demonstrated that levels of DHFR protein and DHFR fusion protein can be induced translationally following MTX treatment of cells. We demonstrated that in response to MTX treatment, DHFR partner protein in a bicistronic construct is induced for longer periods of time when compared with endogenous DHFR and DHFR fusion protein, in vitro and in vivo. Using rapamycin pretreatment followed by MTX treatment, we also devised a strategy to modulate levels of two proteins expressed from a bicistronic construct in a cap-independent manner. To our knowledge, this is the first report demonstrating that levels of proteins in DHFR-based bicistronic constructs can be induced and modulated using MTX and rapamycin treatment.